Regional disparities in the prevalence and correlated factors of myopia in children and adolescents in Gansu, China - Wang, Jinyu; Li, Sheng; He, Shiqi; Feng, Yali; Li, Pu (Frontiers in Medicine, 2024)
Background: Myopia is a significant public health problem across the globe. This study aimed to examine the regional disparity in prevalence and correlated factors of myopia in children and adolescents in two typical regions, Gannan Tibetan Autonomous Prefecture (Gannan Prefecture for short, a Tibetan residential area) and Wuwei City (a Han residential area) in Gansu Province, China, and to provide reference for the prevention and control of regional myopia.The study was a cross-sectional study on children and adolescents in Gansu Province, China. A total of 6187 (Wuwei City:3266, Gannan Tibetan Autonomous Prefecture: 2921) students were selected by stratified cluster sampling. Eye examinations and questionnaires were conducted to the participants. Myopia is defined as a condition in which the spherical equivalent refractive error of an eye is less than or equal to -0.50 D when ocular accommodation is relaxed. χ 2 test and multivariate logistic regression analysis were used to analyze the correlated factors of myopia.The myopia rate of 6187 students was 71.4%, and students had a higher rate of myopia (77.5%) in Wuwei City compared with Gannan Prefecture (64.6%) (P<0.001). The results of multivariate analysis in Wuwei City showed that girls (OR=1.325), junior students (OR=2.542), senior students(OR=4.605), distance between eyes and book less than one foot (OR=1.291), parents with myopia (one, OR=2.437; two, OR=4.453) had higher risks of myopia (all, P<0.05). For Gannan Prefecture, girls (OR=1.477), senior students (OR=1.537), daily time spend doing homework ≥2 h (OR=1.420), distance between eyes and book less than one foot (OR=1.205), mean time continuous eye use (0.25 -<0.5 h, OR=1.345; 0.5 -<1h, OR=1.317; ≥1h, OR=1.313), average daily sleep duration < 8h (OR=1.399), parents with myopia (one, OR=1.852; two, OR=2.913) had higher risks of myopia (all, P<0.05).The prevalence of myopia is at a relatively high level in Gansu Province. The prevalence and risk factors for myopia vary with region.